The Ancient Greeks in the Thought of Arvydas Šliogeris: The Ambiguity of Reception - Gintarė Škėmaitė (Literatūra (Vilnius))
This article examines Šliogeris’ engagement with the Ancient Greeks, focusing on the mature phase of his philosophy, where the concepts of Nihil and Presence are fully articulated. From the outset, Šliogeris’ reception of the Greeks is marked by a distinct ambivalence, oscillating between deep admiration and sharp critique. In this case, rather simultaneous ambiguities of direction are identified, reflecting not just temporal or semantic divides but also an intrinsic tension within his thought. The article analyses the sources of this interpretive instability, questioning what underlies Šliogeris’ positive and negative perspectives on the Greeks and exploring whether these modes hold equal weight or if one predominates. It argues that Šliogeris’ understanding of the Greeks reflects the ambivalence of his central concepts – Nihil and Presence, which represent opposing qualities. For Šliogeris’, the essence of being human lies in being “in between” these conflicting forces. The Greeks, as an early culture, exemplify the interplay of Nihil and Presence in its most genuine form. Therefore, the reception of the Greeks supports Šliogeris’ philosophical theory. This effect stems from the specifics of his thinking; he approaches it with passion and is unafraid of incoherence or repetition.